Genotypic Responses of Upland Rice to an Altitudinal Gradient - Shrestha, S.P. (University of Hohenheim, 2012)
This thesis is based on multi-locational field trials conducted in Madagascar and the greenhouse trials carried out in the University of Hohenheim, Germany in the Crop Water Stress Management Section of the Department of Plant Production and Agroecology in the Tropics and Subtropics. The thesis is submitted together with the enclosed three peer reviewed manuscripts in a partial fulfilment of the requirement for Ph.D. degree at the Faculty of Agricultural Sciences.